2003
DOI: 10.2337/diacare.26.8.2410
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Heterogeneity and Associations of Two Aldose Reductase Gene Polymorphisms With Nephropathy and Retinopathy in Type 2 Diabetes

Abstract: OBJECTIVE -We investigated the phenotypic features of diabetic microvascular complications and their association with a (CA) n microsatellite and a C/T polymorphism at the 5Ј region of the aldose reductase gene (ALR2) in a consecutive cohort of 738 Chinese type 2 diabetic patients.RESEARCH DESIGN AND METHODS -Of the entire patient cohort, 392 were free of diabetes complications, or uncomplicated, 159 had diabetic nephropathy, 66 had diabetic retinopathy, and 121 had both diabetic nephropathy and retinopathy. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 30 publications
3
60
1
1
Order By: Relevance
“…However, this contradicts numerous reports of (1) alleviation, rather than aggravation, of oxidative-nitrosative stress by AR inhibitors in other tissues of diabetic animals as discussed above, and (2) beneficial effects of both AR inhibitors and antioxidants on experimental DN [4,5,14,15]. Furthermore, several groups demonstrated that prevalence of DN depends on (1) erythrocyte AR content, and/or (2) frequency of the z-2 allele of the AR gene, in human subjects with diabetes mellitus [4,67,68]. Homozygosity for the z-2 allele in Type 1 (insulin-dependent) diabetes is associated with an increased expression of the AR gene and DN [67].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this contradicts numerous reports of (1) alleviation, rather than aggravation, of oxidative-nitrosative stress by AR inhibitors in other tissues of diabetic animals as discussed above, and (2) beneficial effects of both AR inhibitors and antioxidants on experimental DN [4,5,14,15]. Furthermore, several groups demonstrated that prevalence of DN depends on (1) erythrocyte AR content, and/or (2) frequency of the z-2 allele of the AR gene, in human subjects with diabetes mellitus [4,67,68]. Homozygosity for the z-2 allele in Type 1 (insulin-dependent) diabetes is associated with an increased expression of the AR gene and DN [67].…”
Section: Discussionmentioning
confidence: 99%
“…Homozygosity for the z-2 allele in Type 1 (insulin-dependent) diabetes is associated with an increased expression of the AR gene and DN [67]. In Type 2 (non-insulin-dependent diabetes), the z-2 allele is also associated with an increased AR activity and nephro-retinopathy [68]. Furthermore, homozygosity for the z-2 allele was recently reported to be associated with classic diabetic glomerulopathy manifested by overexpression of TGF-β1, mesangial cell transdifferentiation by expression of α-smooth muscle actin, and aberrant deposition of collagen type IY, fibronectin, and laminin [69].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of DR is doubled in patients with microalbuminuira, and 6 times higher in the presence of macroalbuminuria [112], suggesting that DN and DR may share common risk factors, including genetic susceptibility factors. Indeed, sev-eral genes have been associated with DR and DN [113][114][115].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Polymorphism in the retinoid-X receptor (RXR) gamma gene has also been associated with DR (OR = 2.388; 95% confidence interval = 1.17-4.875) in Asians with T2D [126]. Polymorphisms in the regulatory region of the aldose reductase (ALR2) gene (encoding the rate-limiting enzyme of the polyol pathway) were associated with susceptibility to DN and DR [114,127]. However, the impacts of these genetic risk factors were modest, and some studies yielded inconsistent findings [128,129].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Plasma creatinine was measured using the Jaffe method on a Dimension AR system (Dade Behring, Deerfield, IL; normal reference range 44 -80 mol/l) (29). Glomerular function was also estimated using the formula proposed by Cockcroft and Gault for creatinine clearance (36), expressed as ml ⅐ min Ϫ1 ⅐ 1.73 m Ϫ2 and calculated as (140 Ϫ age in years) ϫ body wt in kg ÷ 72 ÷ (plasma creatinine in mol/l ÷ 88.4) ϫ 0.85 (if patient was female), and the Modification of Diet in Renal Disease (MDRD) Study Group formula for the GFR (37), expressed as ml ⅐ min Ϫ1 ⅐ 1.73 m Ϫ2 and calculated as 170 ϫ (plasma creatinine in mg/dl) Ϫ0.999 ϫ (age in years) Ϫ0.176 ϫ 0.762 (if patient was female) ϫ (plasma urea in mg/dl) Ϫ0.170 ϫ (plasma albumin in g/dl) 0.318 .…”
Section: Methodsmentioning
confidence: 99%